Decreased telomerase activity and shortened telomere length in infants whose mothers have gestational diabetes mellitus and increased severity of telomere shortening in male infants - Liu, Shuhua; Xu, Liping; Cheng, Yan; Liu, Dehong; Zhang, Bin; Chen, Xianxia; Zheng, Mingming (Frontiers in Endocrinology, 2024)
ObjectiveGestational diabetes mellitus (GDM) is a common complication during pregnancy and increases the risk of metabolic diseases in offspring. We hypothesize that the poor intrauterine environment in pregnant women with GDM may lead to chromosomal DNA damage and telomere damage in umbilical cord blood cells, providing evidence of an association between intrauterine programming and increased long-term metabolic disease risk in offspring.MethodsWe measured telomere length (TL), serum telomerase (TE) activity, and oxidative stress markers in umbilical cord blood mononuclear cells (CBMCs) from pregnant women with GDM (N=200) and healthy controls (Ctrls) (N=200) and analysed the associations of TL with demographic characteristics, biochemical indicators, and blood glucose levels.ResultsThe length of telomeres in umbilical CBMCs in the GDM group was significantly shorter than that in the Ctrl group (P<0.001), and the shortening of telomeres in male infants in the GDM group was more significant than that in the Ctrl group (P<0.001) after adjustment for Pre-pregnancy body mass index (PBMI), Pregnancy weight gain (PGW), and Triglyceride (TG) as confounding factors. In addition, the TE expression level in the GDM group was lower after adjustment. There was no statistically significant difference in oxidative stress hydroxydeoxyguanosine (8-OHdG), malondialdehyde (MDA) and superoxide dismutase (SOD) between the two groups. TL was positively correlated with TE activity, and both were negatively correlated with blood glucose levels. There was no correlation between TL and Gestational age (GA), PBMI, PGW, or TG levels.ConclusionThe poor intrauterine environment in pregnant women with GDM increases telomere attrition and reduces TE activity, which may be potential genetic risk factors for an increased risk of metabolic diseases in offspring later in life due to intrauterine reprogramming.